Ethanol alters mechanosensory habituation in C. elegans by way of the BK potassium channel through a novel mechanism - Nikolas Kokan; Conny Lin; Alvaro Luna; Joani Viliunas; Catharine H. Rankin (PLoS ONE, 2025)
In this research, we investigated how alcohol modulates the simplest form of learning, habituation, in Caenorhabditis elegans. We used our high throughput Multi-Worm Tracker to conduct a large scale study of more than 21,000 wild-type worms to assess the effects of different concentrations of alcohol on habituation of the well-characterized tap withdrawal response. We found that the effect of alcohol on habituation of this reversal response to a repeated mechanosensory stimulus (taps) differed depending on the component of the reversal response assessed. Interestingly, when we examined habituation of response probability on and off alcohol we discovered that alcohol switched the predominant response to tap from a backward reversal to a brief forward movement. Because the large conductance potassium (BK) channel has been shown to be important for the effect of alcohol on behaviour in a variety of organisms, including C. elegans, we investigated whether the C. elegans BK channel ortholog, SLO-1, mediated the effects of alcohol on habituation. We tested several different strains of worms with mutations in slo-1 along with wild-type controls; null mutations in slo-1 made animals resistant to alcohol induced changes in habituation. However, a mutation in the putative ethanol binding site on SLO-1 did not disrupt the impact of ethanol on habituation. Finally, by degrading SLO-1 in different parts of the nervous system we found that the function of SLO-1 in ethanol’s impact on habituation is likely distributed throughout the neural circuit that responds to tap. Based on these results, our main conclusions are 1) ethanol is not a general facilitator or inhibitor of habituation but rather a complex modulator, 2) SLO-1 is critical for the effect of ethanol on habituation, 3) ethanol is interacting (directly or indirectly) with SLO-1 through a novel unidentified mechanism to influence how animals respond to repeated taps.